ACADEMIC LEARNING PROBLEMS AND RORSCHACH INDICES: A RE-REPLICATION - Rodríguez Sutil, Carlos; Ortiz, Pilar; Scott, Ralph (Anales de Psicología / Annals of Psychology)
This study compared the Rorschach responses of male children who were and who were not experiencing learning problems. Whith controls exacted on social class, chronological age, and IQ, the responses of 19 pairs of subjects were examined; group differences in perceptual accuracy, selfconcept, and reactivity were assessed. Despite some differences being small, responses of children with learning problems were characterized by lower perceptual accuracy and lower self-concept. On the other hand, they obtained a D score significatively lower.